Chiron Approach to Formal Synthesis of 8,9-dideoxyneodysiherbaine (MSVIII-19) - Sanchez-Eleuterio, Alma; M. Mastranzo, Virginia; Quintero, Leticia; Sartillo-Piscil, Fernando (Letters in Organic Chemistry, 2017)
Background: The synthesis of biologically active model compounds represents a valuable tool for medicinal chemistry. In this regard, the synthesis of MSVII-19, a structurally simplified model compound of Dysiherbaine, developed by the group of Sasaki, was synthesized with the intention of preparing a powerful agonist or antagonist of glutamate receptor. Therefore, the synthesis of an advanced intermediate in the Sasaki’s synthesis of MSVIII-19 is reported. Methods: Taking advantage of the furanose ring of the diacetone-D-glucose (DAG), the cis-fused hexahydrofuro[3,2-b]pyran ring system of the title compound was constructed by featuring two protocols: SHOWO (sequential hydrolysis-oxidation-Wittig olefination) and RCM (ring closing metathesis). Then, by applying a combined allylation at the anomeric position and a Pd-catalyzed double bond isomerization reaction, the methyl ester group in 1b was installed. Results: The synthesis of an advanced intermediate of MSVIII-19 involves three key procedures: a) SHOWO (sequential hydrolysis-oxidation-Wittig olefination) protocol; b) RCM (ring closing metathesis) reaction; y c) the nucleophilic substitution at the anomeric position. Additionally, with the use of a cheaper starting material (DAG) than that used in the previous synthesis (tri-O-acetyl-D-glucal). The current synthesis is truly competitive with that reported by the Sasaki group. Conclusion: A concise formal total synthesis of the advanced intermediate of MSVIII-19 was achieved. (Current synthesis: 14 steps; previous synthesis 20 steps).
Keywords: ring closing metathesis